Trojans of ambiguity vs resilient regeneration: visual meaning in cities (Construction Economics and Building, 2020)
This paper presents a theoretical framework that helps identify visual sustainability in urban projects and evaluates its relevance for the use, design and making of public space. It is aimed at showing how the process of urban regeneration is far more nuanced and sophisticated than much of today’s building industry allows for. The first part of the article provides an outline of this framework, by drawing from the notion of ambiguity and discussing regeneration around a concept of trojans of ambiguity: by which we simply mean that modern-day regeneration projects are often a confusion of meaning. The framework is then applied to two case studies: Heygate, and Sidewalk Labs Toronto. The Heygate regeneration produced a negative emotionally charged process and social displacement. By contrast Sidewalk Labs Toronto exemplifies a technologically clean start for regeneration, on a site with little social vitality or history. The starting points for each ultimately point to two very different outcomes. Visual sustainability represents ‘the technology before the technology’ and future research must recognise how human needs, not technology, provide the meaning into ‘how’ we may create a successful, smart, and sustainable urban environment.